Experimental investigation of the pressure influence on flame structure of fuel-rich oxy-fuel methane flames for synthesis gas production. (15th February 2021) - Sentko, M.M.; Schulz, S.; Stelzner, B.; Anderlohr, C.; Vicari, M.; Trimis, D.
Abstract: The structure of fuel-rich CH4 /O2 -flames at equivalence ratios in the range of 2.5 ≤ ϕ ≤ 2.9, a preheating temperature of T P = 573 K and pressure in the range of 1 b a r a ≤ p ≤ 5 b a r a was studied experimentally and compared with numerical results using detailed reaction mechanisms. Two measurement techniques, invasive gas sampling (GC/MS) and optical in-situ TDLAS measurements (tunable diode laser absorption spectroscopy), were used to determine temperature and major combustion species (CH4, O2, H2, H2 O, CO and CO2 ). The results showed that the composition of the synthesis gas in the post flame zone strongly depends on ϕ, while p has only a minor influence. Furthermore, the influence of ϕ and p on the phenomena of super-adiabatic flame temperatures (SAFT) was determined by experimentally and numerically investigating temperature and H2 O concentration. The results showed similar trends as for the synthesis gas composition: a strong dependence of ϕ and a minor influence of pressure on the degree of significance of the SAFT phenomena.